Physical characterization and fluidization design parameters of wheat germ - Gili, Renato (2017)
Wheat germ is the embryo of de wheat seed, it contains a high tocopherol and protein content, and highquality proteins and fatty acids. Also, wheat germ has a considerable enzymatic activity that limits itsshelf life. The aims of the study were to physically and sorptionally characterize wheat germ particles,select the more convenient model to describe the relationship between moisture content and wateractivity of wheat germ and to determine their design parameters of thermalfluidization process with air.The principal axes of the particle were measured by image analysis, and their dimensions and geometricparameters were calculated. Four isotherm models werefitted to experimental data. GAB model was themore accurate to explain the experimental data. Thefixed bed density and the void fraction weremeasured. Thefluid-dynamic studies permitted to determine laminar (277.46±17.48) and turbulent(7.79±0.69) coefficients of the Ergun equation and the minimumfluidization velocity (0.35±0.02 m/s).